The Influence of Perum Damri Service Quality On Customer Satisfaction In Makassar City - Niswaty, Risma; Lestari, Andiny Mulya; Akib, Haedar (PINISI Discretion Review, 2023)
The objectives of the research in this title are: 1), To analyze how much service quality at Perum Damri Makassar City is, 2) To analyze how much customer satisfaction Perum Damri Makassar City has, and, 3) To analyze how much influence Perum Damri service quality has on customer satisfaction in Makassar City. The type of research used is quantitative. The population of this study is users of Damri transportation services in Makassar City in 2020-2022 with a total of 1740 people. The research sample consisted of 174 people. The data collection techniques for this research are observation, questionnaires, and documentation. The data analysis used is multiple linear regression. The results of the research showed that processing the data for each respondent's answers resulted in 62% uncertain answers. The first problem formulation shows the results that the service quality of Perum Damri in Makassar City can influence the service benchmark (X) of Perum Damri in Makassar City. The second problem formulation shows that the affirmative answer reaches 55% of the benchmarks used, thus affecting customer satisfaction regarding interest in using Damri Makassar City transportation services. Meanwhile, the third problem formulation shows that the independent sample T-test output obtained a Sig-(2-tailed) value of 0.000 < 0.05, so it is in accordance with the basis for decision-making in the independent sample T-test, which concludes that there is a difference. Making decisions based on the Fcount and Ftable output values above, obtained an Fcount value of 0.071.